Comprensión de la moda y la media aritmética - Naire Guimaray, Alberto Cipriano (2018)
Through this Learning Session, it is intended to build in the students an ability for Solving daily life problems and face problematic situations in their future as a value person for society. It will take into account the way in which the students through Solving Problems of the Ability Solve Problems Management Data and Uncertainty, referred to the fashion knowledge and the Arithmetic media. Problem solving has didactic processes to follow such as: Familiarization or problem comprehention. Search and strategy execution. Socialization with their representations. Formalization and reflection. Planning other problems. Understanding the arithmetic media and mode in data management is vital importance in determining the frequency and statiscal average data.